2018
DOI: 10.1152/ajpgi.00268.2017
|View full text |Cite
|
Sign up to set email alerts
|

Functional role and therapeutic targeting of microRNAs in inflammatory bowel disease

Abstract: Inflammatory bowel diseases (IBD) are chronic inflammatory gastrointestinal diseases, primarily consisting of ulcerative colitis and Crohn's disease. The complex nature of the disease, as well as the limited therapeutic options characterized by low efficiency and major side effects, highlights the importance of developing novel strategies of therapeutic intervention in IBD. Susceptibility loci related to IBD are present only in a small percentage of IBD patients, implying that epigenetic modifications could in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 69 publications
0
32
0
2
Order By: Relevance
“…We and others have previously described the utility of miRNAs as biomarkers in IBD. 14 , 16–18 Adding to our previous miRNA studies in pediatric IBD, here we have now identified 8 serum miRNA biomarkers that are associated with clinical response to anti-TNF-α therapy (after weeks) and GC treatment (after weeks) 14 but (with the exception of miR-26b) not with shorter courses of GCs (after days). These are miR-126, miR-146a, miR-146b, miR-26a, miR-26b, miR-320a, miR-454, and let-7c.…”
Section: Discussionmentioning
confidence: 85%
“…We and others have previously described the utility of miRNAs as biomarkers in IBD. 14 , 16–18 Adding to our previous miRNA studies in pediatric IBD, here we have now identified 8 serum miRNA biomarkers that are associated with clinical response to anti-TNF-α therapy (after weeks) and GC treatment (after weeks) 14 but (with the exception of miR-26b) not with shorter courses of GCs (after days). These are miR-126, miR-146a, miR-146b, miR-26a, miR-26b, miR-320a, miR-454, and let-7c.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, identification of IBD-associated miRNA autophagic networks and exploration of specific miRNAs as targets for the treatment of IBD is very important. There are two completed phase I trials (NCT00688012 for a single ascending dose and NCT00979927 for multiple ascending doses; drug: SPC3649) funded by Santaris Pharma related to a locked nucleic acid- (LNA-) modified oligonucleotide that specifically inhibits endogenous miR-122, resulting in prolonged dose-dependent reductions in hepatitis C virus (HCV) RNA levels without evidence of viral resistance [ 25 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several review articles to date have discussed the role of miRNAs in IBD [ 8 , 16 , 18 , 19 , 21 25 ], However, there are no reviews that focus on the IBD field and on miRNAs that regulate autophagy and associated pathways. Elucidation of the interaction between miRNAs and autophagy in IBD-specific mechanisms will help to explain the occurrence, development, and future molecular targets of IBD therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Hong et al [109], via RNA-seq, pinpointed differences between the inflamed and non-inflamed intestinal mucosa of CD patients and healthy controls. Of high interest in recent years is the study of noncoding RNAs and their role, as depicted in reviews and original articles [110][111][112][113][114][115][116].…”
Section: Transcriptomics In Ibdmentioning
confidence: 99%